2020
DOI: 10.33087/jiubj.v20i2.926
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Obesitas dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Sidomulyo Rawat Inap

Abstract: Obesity is a condition where excessive accumulation of body fat tissue can cause serious health problems such as hypertension. Obesity and hypertension is a multifactorial disease. Imbalance between consumption of calories and energy needs stored in the form of fat which causes inactive fat tissue so that increased work heart load. As a result of obesity, sufferers tend to suffer from cardiovascular disease. Objective: To determine the relationship of obesity to hypertension in the work area of Sidomulyo Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Supporting research has shown that obesity has a 2,869 times higher risk of developing hypertension than individuals with normal nutritional status (Akbar & Isfandiari, 2018). Similar studies have stated that obesity has a 2,23 times risk of hypertension than those who are not obese (Asyfah et al, 2020). The prevalence of hypertension increases by 87%, and high BMI levels are associated with obesity (Landi et al 2018).…”
Section: Resultsmentioning
confidence: 89%
“…Supporting research has shown that obesity has a 2,869 times higher risk of developing hypertension than individuals with normal nutritional status (Akbar & Isfandiari, 2018). Similar studies have stated that obesity has a 2,23 times risk of hypertension than those who are not obese (Asyfah et al, 2020). The prevalence of hypertension increases by 87%, and high BMI levels are associated with obesity (Landi et al 2018).…”
Section: Resultsmentioning
confidence: 89%
“…Obesitas sendiri sudah dapat mengakibatkan kelemahan otot jantung atau cardiomyopathy, sehingga mengganggu daya pompa jantung (Husnah, 2012). Salah satu upaya untuk mencegah hipertensi yaitu dengan mengetahui berat badan ideal agar bisa meminimalisir faktor risiko dengan menggunakan rumus BMI (Asyfah et al, 2020). BMI merupakan alat sederhana untuk memantau status gizi orang dewasa khususnya yang berkaitan dengan kekurangan dan kelebihan berat badan, dengan demikian mempertahankan berat badan normal memungkinkan seseorang dapat mencapai usia harapan hidup lebih panjang.…”
Section: Jenis Kelaminunclassified
“…Kebiasaan merokok berperan menyebabkan terjadinya hipertensi karena rokok mengandung nikotin dan karbon monoksida yang berpengaruh terhadap tekanan darah. Nikotin dapat meningkatkan asam lemak, mengaktivasi trombosit, memicu arteriosklerosis dan penyempitan pembuluh darah (El Islamy, Simamora, Syahri, Zaini, Sagala, & Dwi, 2023;Lubis, Afifah, Abidin, Shiddiq & Ismah, 2023).…”
Section: Pembahasanunclassified